PENGARUH PUPUK GANDASIL-D DAN BERBAGAI LIMBAH PERKEBUNAN KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA. - Nanang Eko Nurcahyo; Erlida Arian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to determine the effect of fertilizers Gandasil-D and a variety of waste oil pail plantations as well as to get the best treatment on the growth of oil palm seedlings in the main nursery. The research was carried out for 3 months starting from September 2014 until December 2014. This research was conducted in Greenhouse Agriculture Faculty University of Riau Campus Bina Widya KM 12.5 Simpang Baru Tampan, Pekanbaru. This research was conducted experiments using completely randomized factorial design, which consisted of 2 factors with 3 replications. The first factor is fertilizers Gandasil-D consisted of 3 levels, G1 = 1.0 g/l, G2 = 2.0 g/l, G3 = 3.0 g/l, and the second factor is the variety of waste oil palm plantations consist of 4 level, L0 = without treatment, L1 = TKKS 20 ton/ha, L2 = LCPKS 0.64 l/polybag, L3 = a combination of 10 ton/ha TKKS + 0.32 l/polybag LCPKS. There are 12 combined treatment and 36 units of trial and each experimental unit contained two plants so that over all there are 72 plants. Results of analysis of variance followed by Duncan’s New Multiple Range Test (DNMRT) at 5%. The results showed that the interaction of a mixture Gandasil-D and a variety of waste oil palm plantations in the treatment of 3 g/l Gandasil-D and a combination of 10 ton/ha TKKS + 0.32 l/polybag LCPKS, significant effect on plant height increment, increment the number of leaves, the ratio of the canopy and roots, and root volume, and there is not the real effect on the stump diameter and dry weight. Keywords:Gandasil-D, Waste Oil Palm, Main Nursery